STRATEGI GURU DALAM MENGATASI KEJENUHAN BELAJAR PAI PADA SISWA KELAS XI DI SMAN 1 TIGO NAGARI KABUPATEN PASAMAN - Derita Ningsih; Wedra Aprison; Salmi Wati; Junaidi Junaidi (Universitas Pahlawan Tuanku Tambusai, 2022)
The lack of PAI teacher methods in providing learning explanations when students participate in the PAI learning process in class shows that some students experience boredom. In this case, the teacher has tried to overcome the boredom of the students concerned, but in reality there are still problems related to students saturation in learning PAI. This can be seen from the situation of students who pay less attention to the explanation given by the teacher, talk to their classmates when the teacher explains, sleep in the classroom when learning takes place, and often go in and out when the teacher explains the material. The purpose of this study is to see the teacher’s strategy to overcome the saturation of learning PAI in students.To find out the teacher’s strategy to overcome the boredom of learning PAI, qualitative research is the right thing. The data needed in this study is in the form of teacher actions or strategies in overcoming the saturation of learning PAI using interviews and observations. Because this study looks at the teacher’s strategy, the teacher himself cannot be left as the main information and the students as the supporting informants. After the data is collected, data processing and data analysis are carried out. Data reduction, data presentation and data verification are techniques that the author uses to analyze the data. Furthermore, the technique of guaranteeing the validity of the data or triangulation is carried out. The data triangulation technique that the author uses is source triangulation and technical triangulation.Based on the results of the teacher’s strategy research in overcoming the saturation of learning PAI in class XI students at SMAN 1 Tigo Nagari, Pasaman Regency, it can be seen from observations and interviews with PAI teachers and students that there areseveral factors that cause borendom to learn PAI experienced by student of class XI IPS 1 and 2. The factors are physical fatique, problems of time and study hours, learning methods or methods that are less varied and monotonous learning atmosphere. Keywords: Strategy, PAI Teacher, Learning Saturation